Project Cost Analysis Using the Earned Value Method on the Bagor Bridge Replacement Project in Situbondo Regency - Yonandika Pandu Putranto; Andi Patriadi; Sajiyo Sajiyo (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Delays in project implementation are caused by a lack of good control so that it affects the cost and completion time. The purpose of the study is to determine or predict how much a project will cost at the time of implementation and to determine the effectiveness of project control using the Earned Value Method. Aspects of project implementation time in weeks 2,4,5,9,11,13,16,17, 18,20,21,24 are slower than the planned schedule, this is indicated from the Schedule Variant (SV) indicator. While the performance of the project implementation time in week 3,6,7,8,10,12,14,15,19,22 is faster than the plan schedule, this is indicated by the Schedule Variant (SV) is positive. While the cost performance aspects of project implementation from week 6,9,11,13,17,19,22,23 incurred costs greater than the plan cost, this is indicated from the Cost Variant (CV) indicator is negative. Whereas in weeks 7,8,10,12,14,15,16,18,20,21, 24 incurred costs less than the plan cost, this is indicated by a positive Cost Variance (CV) indicator. The calculation results obtained from the effectiveness value of 1.603 for controlling the cost and time of the project using the Earned Value Method. In other words, the results of the effectiveness value greater than 1 (one) can be said to control the construction project of the Situbondo Regency bagor bridge very effectively using the Earned Value method.